Images of Priesthood and Monasticism in the Works of John Chrysostom: Rhetoric and Historical Reality - Yuliia Rozumna (Наукові записки НаУКМА: Філософія та релігієзнавство)
The article provides a comparative analysis of the attitude to priests and monks, the manifestations of which can be found in the works of the outstanding thinker and theologian, representative of patristics, John Chrysostom (347–407 A. D.). It is shown that depending on the purpose of each specific work, he used his own rhetorical abilities in different ways when speaking about priests and monks. When Chrysostom considered each of these figures separately, without comparing them with each other, he certainly showed considerable elevation. For example, when he wanted to exalt the exploits of monks and virgins, he did it in the most refined way. At the same time, in the treatise “Six Discourses on the Priesthood,” while highly evaluating the functions and role of priests, he downplayed the role and importance of monks. In particular, in the last part of this work, Chrysostom portrays the figure of a monk as a kind of egoist who thinks only about his own salvation and has no connection with the outside world. In order to clarify the nature of this duality, we examine the uncertainty and variability in the nature and status of monasticism in the first centuries of Christianity, in particular, we pay attention to the complex nature of the monastic movement in the 4th century, when Chrysostom lived and worked. The historical comparison we have made allows us to assert that in those times, when the Church institution was being formed and its integration into society was still ongoing, the institution of the priesthood had already acquired a fairly stable (“routinized”) charisma, while monasticism had not yet undergone such “routinization.” But, as shown in the article, in general, the institution of monasticism was of great importance for the early Church. Based on this, we conclude that the downplaying of the image of monasticism, which can be seen in the “Six Conversations on the Priesthood,” did not reflect reality in its entirety, but the specific rhetorical intentions of the author of this treatise, due to the specifics of the historical moment.